Methods to Improve Lithium Metal Anode for Li-S Batteries - Xiong, Xiaosong; Yan, Wenqi; You, Chaolin; Zhu, Yusong; Chen, Yuhui; Fu, Lijun; Zhang, Yi; Yu, Nengfei; Wu, Yuping (Frontiers in Chemistry, 2019)
Lithium-sulfur (Li-S) battery has received a lot of attention because it is characterized by high theoretical energy density (2600 Wh / kg) and low cost. Though many works on the "shuttle effect" of polysulfide have been investigated, lithium metal anode is a more challenging problem, which leads to a short life, low coulombic efficiency and safety issues related to dendrites. As a result, the amelioration of lithium metal anode is an important means to improve the performance of lithium sulfur battery. In this paper, the improvement methods on lithium metal anode for lithium sulfur batteries, including adding electrolyte additives, using solid and/or gel polymer electrolyte, modifying separators, applying a protective coating, and providing host materials for lithium deposition, are mainly reviewed. In addition, some challenging problems and the further promising directions are also pointed out for future research and development on lithium metal for Li-S battery.